Antibiofilm effect of cleaning agents for ocular prostheses - Andreotti, A. M. [UNESP] (2023)
Introduction. This study aimed to evaluate the antibiofilm effect of different agents (neutral soap, 4% chlorhexidine, Efferdent effervescent tablets, 1% triclosan, and citronella essential oil) used for ocular prosthesis cleaning. Material and Methods. Biofilms of S. aureus and S. epidermidis were formed on 60 ocular prosthesis acrylic resin specimens. The specimens were cleaned with the studied agents with different techniques. Microorganism counting was performed. Data were submitted to ANOVA and HSD Tukey-Kramer (p<.01). Results. When compared to the control group, all cleaning protocols promoted a reduction in growth of microorganisms. The 4% chlorhexidine, effervescent tablets, and 1% triclosan cleaning agents eliminated biofilm in all groups. Conclusion. Therefore, immersion in 4% chlorhexidine, effervescent tablets, and 1% triclosan could be the best protocols indicated for ocular prosthesis cleaning due to their ability to eliminate biofilm.